2020
DOI: 10.1002/ange.202006722
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Transfer Kinetics of Adsorbed Hydroxyl as a Descriptor of Alkaline Hydrogen Evolution Reaction

Abstract: The key descriptor that dominates the kinetics of the alkaline hydrogen evolution reaction (HER) has not yet been unequivocally identified. Herein, we focus on the adsorbed hydroxyl (OHad) transfer process (OHad + e− ⇄ OH−) and reveal its crucial role in promoting the overall kinetics of alkaline HER based on Ni/Co‐modified MoSe2 model catalysts (Ni‐MoSe2 and Co‐MoSe2) that feature almost identical water dissociation and hydrogen adsorption energies, but evidently different activity trends in alkaline (Ni‐MoSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…As displayed in Figure S29b, the Ru/C owned a more negative potential than that of Ru SAs‐SnO 2 /C in 1.0 M KOH. The slightly negative surface charge on the Ru SAs‐SnO 2 /C indicated that the strong adsorption strength between adsorption site and OH ad hindered the OH ad transfer process (OH ad +e − OH − ) [3] . The above tests were performed to evaluate their ability for OH‐adsorption under positive potential and without external voltage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As displayed in Figure S29b, the Ru/C owned a more negative potential than that of Ru SAs‐SnO 2 /C in 1.0 M KOH. The slightly negative surface charge on the Ru SAs‐SnO 2 /C indicated that the strong adsorption strength between adsorption site and OH ad hindered the OH ad transfer process (OH ad +e − OH − ) [3] . The above tests were performed to evaluate their ability for OH‐adsorption under positive potential and without external voltage.…”
Section: Resultsmentioning
confidence: 99%
“…However, the influence of adsorbed hydroxyl (OH ad ) on active sites has been paid less attention. Principally, the Volmer step (H 2 O+e − H ad +OH − ) can be divided into H 2 O H ad +OH ad and OH ad +e − OH − [3] . (H ad : the adsorbed hydrogen atom).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The hydrogen evolution reaction (HER) kinetics in alkaline medium is much slower than that in acid solution, due to more complex steps of adsorption and dissociation of water in an environment full of hydroxyl (OH − ) disturbance. 3,4 According to the Arrhenius equation, we can deduce the kinetics energy barrier (E a ) by designing suitable catalysts or increase the reaction temperature (T) to boost the alkaline HER kinetics. Few-layered Ti 3 C 2 T x MXenes have been confirmed as ideal substrates to disperse and load catalytically active material, as they show the advantages of better electron conductivity and anti-interference of hydroxyls by their surface electronegativity.…”
Section: Introductionmentioning
confidence: 99%
“…Water electrolysis in alkaline medium has been regarded as a promising approach to achieve large-scale renewable hydrogen production. , The hydrogen evolution reaction (HER) kinetics in alkaline medium is much slower than that in acid solution, due to more complex steps of adsorption and dissociation of water in an environment full of hydroxyl (OH – ) disturbance. , According to the Arrhenius equation, we can deduce the kinetics energy barrier ( E a ) by designing suitable catalysts or increase the reaction temperature ( T ) to boost the alkaline HER kinetics. Few-layered Ti 3 C 2 T x MXenes have been confirmed as ideal substrates to disperse and load catalytically active material, as they show the advantages of better electron conductivity and anti-interference of hydroxyls by their surface electronegativity. Transition metal phosphides (TMPs) have been thought as one kind of promising alternatives for noble metal platinum in alkaline HER catalysis, , because their diversity (rich stoichiometric components, easy doping by heteroatoms, controllable phase transitions, etc .)…”
Section: Introductionmentioning
confidence: 99%
“…The rst-principles calculations show that amorphous phosphate and oxides can produce a large number of dangling bonds on the surfaces of the material, making them promising candidates for electrocatalysis and power storage. 16,17 Meanwhile, the amorphous phase reduces the interfacial transport barrier and increases charge storage sites to dredge carriers at the interface. Zhang et al recommended amorphous Co-Ni pyrophosphates as a battery-type electrode, which proved to possess excellent specic capacity and high cycling stability.…”
Section: Introductionmentioning
confidence: 99%